2022
DOI: 10.1097/bpo.0000000000002294
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis of Developmental Dysplasia of the Hip From Hip Ultrasonography Images With Deep Learning Methods

Abstract: Background: Hip ultrasonography is very important in the early diagnosis of developmental dysplasia of the hip. The application of deep learning-based medical image analysis to computer-aided diagnosis has the potential to provide decision-making support to clinicians and improve the accuracy and efficiency of various diagnostic and treatment processes. This has encouraged new research and development efforts in computer-aided diagnosis. The aim of this study was to evaluate hip sonograms using computer-assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…Previous studies in the literature have also reported that better results are obtained with the VGG-16 model. [7,14,24] Femoroacetabular impingement is recognized as one of the important causes of secondary hip osteoarthritis. It should be kept in mind in the differential diagnosis of diseases such as femoral head avascular necrosis and rheumatic diseases causing pain originating from the hip joint, which can be seen in young individuals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies in the literature have also reported that better results are obtained with the VGG-16 model. [7,14,24] Femoroacetabular impingement is recognized as one of the important causes of secondary hip osteoarthritis. It should be kept in mind in the differential diagnosis of diseases such as femoral head avascular necrosis and rheumatic diseases causing pain originating from the hip joint, which can be seen in young individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the literature have also reported that better results are obtained with the VGG-16 model. [ 7 , 14 , 24 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…La aplicación de algoritmos de aprendizaje profundo ya ha demostrado su eficacia en aumentar la pre-cisión diagnóstica y en reducir la subjetividad que naturalmente acompaña a la interpretación humana de las imágenes médicas. En estudios específicos, como se reporta en la literatura (Atalar et al, 2023), se han comparado diversas arquitecturas de redes neuronales, incluyendo VGG-16, ResNet-101, Mo-bileNetV2 y GoogLeNet, logrando también resultados prometedores con modelos preentrenados como VGG-19. Estas arquitecturas son ampliamente reconocidas en el campo de la visión por computadora y han mostrado su potencial en el análisis de imágenes médicas.…”
Section: Introductionunclassified